Litigation and Penology of Pedophilia in the Perspective of Indonesian Conventional and Islamic Laws - Nur, Iffatin; Teguh, Teguh; Fajarwati, Hiba (Analisis: Jurnal Studi Keislaman, 2022)
The high number of pedophilic incidences in Indonesia is partly due to the lack of community’s social control and the weak supervision of the litigation and penological processes. Considering the impact of pedophilia to victims including long-term trauma, injury, and socio-moral damage that tends to be acute and dangerous, intensive monitoring of both litigation and penological processes must be carried out on a massive scale to ensure and maximize the sustainable protection for children which guarantees and protects their rights so they can live, grow, develop, and participate optimally appropriate to human dignity and integrity as well as get protection from any form of violence and discrimination act. This empirical-normative-juridical qualitative study uses emic and etic approaches; the data analysis refers to the explication technique developed by Von Eckartsberg, Wertz, and Schweitzer, starting with data interpretation and continuing with the integration of interview results and normative-juridical analysis. The results of the study show that the litigation and penology of pedophilia are in line with the Indonesian conventional law and in accordance with the objectives of Islamic law (maqasid shari’ah) eventhough at its penological aspect it is not pretty optimal yet.